Area‐Selective Atomic Layer Deposition on Functionalized Graphene Prepared by Reversible Laser Oxidation. Issue 29 (3rd September 2022) - Mentel, Kamila K.; Emelianov, Aleksei V.; Philip, Anish; Johansson, Andreas; Karppinen, Maarit; Pettersson, Mika
Abstract: Area‐selective atomic layer deposition (ALD) is a promising "bottom‐up" alternative to current nanopatterning techniques. While it has been successfully implemented in traditional microelectronic processes, selective nucleation of ALD on 2D materials has so far remained an unsolved challenge. In this article, a precise control of the selective deposition of ZnO on graphene at low temperatures (<250 °C) is demonstrated. Maskless femtosecond laser writing is used to locally activate predefined surface areas (down to 300 nm) by functionalizing graphene to achieve excellent ALD selectivity (up to 100%) in these regions for 6‐nm‐thick ZnO films. The intrinsic conductive properties of graphene can be restored by thermal annealing at low temperature (300 °C) without destroying the deposited ZnO patterns. As the graphene layer can be transferred onto other material surfaces, the present patterning technique opens new attractive ways for various applications in which the functionalized graphene is utilized as a template layer for selective deposition of desired materials. Abstract : Laser‐induced two‐photon oxidation activates locally graphene for atomic layer deposition (ALD). The ALD precursors exhibit superior affinity toward functionalized graphene and selectively create metal oxide films on activated arbitrary patterns. The conductive properties of graphene, altered by laser exposure, are restored by thermal annealing step. The procedure enables improved fabrication of graphene‐based electronic devices.